2003
DOI: 10.1097/01.wcb.0000061881.75234.5e
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and Microglia in Central Nervous System Injury: Are They Helpful or Harmful?

Abstract: Summary:Inflammation has been widely perceived as participating in the etiology of acute and chronic neurodegenerative conditions. Accordingly, in the context of traumatic injuries or chronic neurodegenerative diseases in the central nervous system (CNS), activated microglia have been viewed as detrimental and attempts have been made to treat both conditions by antiinflammatory therapy. Recent studies have suggested that microglia act as stand-by cells in the service of both the immune and the nervous systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(33 citation statements)
references
References 109 publications
(123 reference statements)
1
32
0
Order By: Relevance
“…Here, we have demonstrated that an inflammatory response in the tissue environment that encounters newborn neurons during neurogenesis in the adult brain is detrimental for their survival. However, microglia activation after brain damage can probably also have beneficial effects by promoting other aspects of regeneration, e.g., through the release of neurotrophic molecules (38,39). It is conceivable that the relative importance of the harmful and helpful actions of microglia under various circumstances will determine the behavioral consequences of brain inflammation and its inhibition by drugs like minocycline.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have demonstrated that an inflammatory response in the tissue environment that encounters newborn neurons during neurogenesis in the adult brain is detrimental for their survival. However, microglia activation after brain damage can probably also have beneficial effects by promoting other aspects of regeneration, e.g., through the release of neurotrophic molecules (38,39). It is conceivable that the relative importance of the harmful and helpful actions of microglia under various circumstances will determine the behavioral consequences of brain inflammation and its inhibition by drugs like minocycline.…”
Section: Discussionmentioning
confidence: 99%
“…7) Therefore, antiinflammatory agents and/or inhibitors of NO production are considered to be potentially beneficial for the managements of CNS disorders such as stroke and Alzheimer's disease (AD). 6,7) In the present study, we attempted to characterize pharmacological actions of T. farfara in the CNS using primary cultured rat cortical cells. According to our preliminary data, the hexane-soluble fraction of T. farfara exhibited cytotoxicity in cortical cells.…”
mentioning
confidence: 99%
“…The expression of inflammatory mediators including cyclooxygenase enzymes and their products is shown to be increased in many acute and chronic neurodegenerative diseases, and several of these factors are found to contribute directly to neuronal injury. 6) Moreover, excess NO has been viewed as a major agent of neuropathology, by directly or indirectly promoting oxidative and nitrosative stresses. 7) Therefore, antiinflammatory agents and/or inhibitors of NO production are considered to be potentially beneficial for the managements of CNS disorders such as stroke and Alzheimer's disease (AD).…”
mentioning
confidence: 99%
“…It tries to maintain the homeostasis that has been disturbed due to injury or any other damage. The glial cells (especially astrocytes and microglia) play an important role in the process of neuroinflammation (Streit 2002;Schwartz 2003;Patro and Patro 2004;Patro et al 2005) and respond rapidly following neuronal injury. While astrocyte provides nutritional support to the neurons, the microglia comes close to the injured neurons, secrete neuroprotective cytokines and renders synaptic stripping.…”
Section: Introductionmentioning
confidence: 97%